SOCİAL MARKETİNG AND ALLEVİATİON OF POVERTY (Third Sector Social Economic Review, 2013)
Poverty is continuing to be an embarrassing and challenging issue for mankind all over the world. As in the other parts of the world the poorest segment of the Turkish population are people living in rural areas engaged in agriculture. Rural development policies aimed at poverty alleviation have been implementing in Turkey since 1980. However; these policies have lacked social marketing approach resulting in success in some areas and failure in others. Use of social marketing as a tool to combat poverty in rural areas is discussed in this article.
Keywords: Poverty alleviation; Rural Population; Social Marketing and Turkey